Pengaruh Kepemimpinan Kepala Sekolah dan Komunitas Belajar Terhadap Kualitas Pembelajaran di SD Negeri Se-Kecamatan Kunduran - Hesti Pandu Wismasita; Soedjono Soedjono; Harto Nuroso (Cetta: Jurnal Ilmu Pendidikan, 2026)
The quality of learning in elementary schools in Kunduran District, Blora Regency, remains significantly deficient. Problems were identified in teacher behavior during instruction, student activities, the learning climate, and the learning system. Factors influencing the low quality of learning are principal leadership and the learning community. This study aims to determine the influence of principal leadership and the learning community on the quality of learning in elementary schools in Kunduran District, Blora Regency. The approach used in this study was quantitative. The study population was all elementary schools in Kunduran District, Blora Regency. The sample size was 172 teachers. Prerequisite analysis tests included normality, linearity, homogeneity, multicollinearity, and heteroscedasticity tests. Hypothesis testing included simple regression and multiple regression tests. The results showed that: (1) principal leadership significantly influenced learning quality by 35.5%; (2) learning community significantly influenced learning quality by 43.7%; and (3) principal leadership and the learning community significantly influenced learning quality by 51.8%. It is recommended that teachers improve their skills in implementing learning, starting from the skills of opening lessons to closing learning activities.